The effect of the COVID-19 pandemic on the mental health of Division III athletes - Schlenker, K.; O'Grodnik, M. (ONU Student Research Colloquium, 2021)
Context: Mental disorders are common in athletes and the COVID-19 pandemic has presented unique challenges for this population. Stress has been shown to increase injury risk; therefore it is possible that coronavirus could increase injury risk if it causes mental health to decrease. Objective: The purpose of this study aims to assess the impact of the COVID-19 pandemic on Ohio Northern University DIII athletes. This will be done to understand the new challenges these athletes are facing and to understand where they are mentally and physically. This will be done to ensure that they are getting their needs addressed along with their health both mentally and physically are being protected. Design: This study will be done as a cross sectional survey to look at the perspectives of DIII Collegiate athletes, regarding their concerns, worries, feelings, and challenges they have experienced from the cancelation of sport seasons. This will also examine the other impacts that the coronavirus has had on their athletic team involvement. Setting: This study will be conducted as a google form sent to these athletes via email that they are able to answer at a time that is convenient to them. Patients or Other Participants: A convenience sample will be utilized with men and women soccer, basketball and lacrosse athletes at Ohio Northern University. The only criteria will be that the participants are from one of these sports teams and are 18 years or older. Participation will be voluntary, and all prospective participants will be emailed a link to the survey. Interventions: The survey will be administered through a Google Forms survey link that will be emailed to individuals. All responses will be kept confidential, and no identifiable information will be collected. The survey will consist of multiple choice questions inquiring about athlete`s mental health status related to the COVID-19 pandemic and its effects on their sport participation. Main Outcome Measures: Mental health outcomes will be examined following survey responses to identify a possible relationship between COVID-19 and mental health in DIII collegiate athletes.